Secondary Solidification Behavior of A356 Aluminum Alloy Prepared by the Self-Inoculation Method - Ming Li (Metals, 2017)
Semisolid slurry of A356 aluminum alloy was prepared by Self-Inoculation Method, and the secondary solidification behavior during rheo-diecasting forming process was researched. The results indicate that the component with non-dendritic and uniformly distributed microstructures can be produced by Rheo-Diecasting (RDC) process (combining Self-inoculation Method (SIM) with High Pressure Die Casting (HPDC)). The isothermal holding time of the slurry has large effect on primary particles, but has little effect on secondary particles. Growth rate of the primary particles in the isothermal holding process conforms to the dynamic equation of Dt3 − D03 = Kt. The suitable holding time for rheo-diecasting of A356 aluminum alloy is 3 min. During filling process, the nucleation occurs throughout the entire remaining liquid, and nuclei grow stably into globular particles with the limited grain size of 6.5μm firstly, then both α1 and α2 particles appear unstable growth phenomenon due to the existence of constitutional undercooling. The average particle sizes and shape factors of both α1 and α2 are decreasing with the increase of filling distance due to different cooling rate in different positions. The growth rate of the eutectic in RDC is 4 times faster than HPDC, which is mainly due to the limitation of α2 particles in RDC process. The average eutectic spacings are decreasing with the increase of filling distance.